Nursing care in Systemic Lupus Erythematosus - Avendaño Zamora, Paola Karely (2023)
Systemic Lupus Erythematosus (SLE) being a multisystemic chronic disease and, in addition to having a wide range of symptoms, requires specialized joint work by the multidisciplinary health team for the complete well-being of the patient. The nursing professional is a key player in the management of the different clinical aspects of SLE, which will be reflected in providing holistic care that is of quality and warmth, as well as in promoting maximum autonomy in the health-disease process. of the patient. Given the different needs of the patient, the main nursing diagnoses of the needs of the patient with SLE have been established, through the nursing interventions NANDA, NIC and NOC. In this sense, the objective of the essay is to describe the interventions of the nursing professional and of the multidisciplinary health team to the patient with SLE.